Mode-Dependent Effects of a Piggyback Throttle Controller on Torque and Power in a 1500 cc EFI Engine - Farhat Ramadhan Ilza; Nuzul Hidayat; Toto Sugiarto; Iffarial Nanda; Jackly Muriban (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2026)
The rising adoption of aftermarket devices in the car modification industry has heightened interest in the piggyback throttle controller as an effective means of modifying throttle response without substituting the original ECU. Nonetheless, its impact on torque and power remains inadequately substantiated through controlled experimentation. This study experimentally assessed the impact of a 9-Drive piggyback throttle controller on the performance parameters of a 2011 Toyota Yaris 1500 cc EFI engine utilizing a chassis dynamometer. The car underwent testing under four conditions: no treatment, Standard mode, F1 mode, and ECO mode, with each condition replicated three times. The findings indicated that F1 mode generated the maximum average torque, attaining 177.13 Nm, which was 15.03 Nm greater than the untreated condition. Conversely, ECO mode yielded the highest average power at 98.60 HP, whereas Standard mode exhibited just negligible variations in both metrics. The data demonstrate that the controller did not produce a consistent performance enhancement across all modes, but instead altered the engine's output characteristics in a mode-dependent fashion. Under the current testing conditions, F1 mode exhibited a more pronounced torque-oriented response, while ECO mode demonstrated marginally greater power output. The findings indicate that a piggyback throttle controller can alter engine response characteristics, however its impact must be assessed in relation to the chosen mode and the particular performance metric under evaluation.